Epidermal growth factor receptor blockers for the treatment of ovarian cancer - Morrison, J; Thoma, C; Goodall, R; Lyons, T; Gaitskell, K; Wiggans, A; Bryant, A (John Wiley & Sons, Ltd, 2018)
Background: This is an update of a previously published version of the review (Issue 10, 2011). Epithelial ovarian cancer (EOC) is the seventh most common cause of cancer death among women worldwide. Treatment consists of a combination of surgical debulking and platinum‐based chemotherapy. Between 55% and 75% of women who respond to first‐line therapy experience relapse within two years. Second‐line chemotherapy is palliative and aims to reduce symptoms and prolong survival. Improved understanding about the molecular basis of EOC has led to the development of novel agents, such as epidermal growth factor receptor (EGFR) tyrosine kinase inhibitors and anti‐EGFR antibodies. Objectives: To compare the effectiveness and harmful effects of interventions that target the epidermal growth factor receptor in the treatment of epithelial ovarian cancer (EOC). Search methods: We searched the Cochrane Gynaecological Cancer Group Trials Register, the Cochrane Central Register of Controlled Trials (CENTRAL; 2010, Issue 4), MEDLINE, and Embase up to October 2010. We also searched registers of clinical trials, abstracts of scientific meetings, and reference lists of included studies, and we contacted experts in the field. This update includes further searches up to September 2017. Selection criteria: Randomised controlled trials (RCTs) comparing anti‐EGFR agents with or without conventional chemotherapy versus conventional chemotherapy alone or no treatment in women with histologically proven EOC. Data collection and analysis: Two review authors independently abstracted data, assessed risk of bias, and performed GRADE assessment. Main results: From 6105 references obtained through the literature search and an additional 15 references derived from grey literature searches, we identified seven RCTs that met our inclusion criteria and included 1725 participants. Trial results show that after first‐line chemotherapy is provided, maintenance treatment with erlotinib (EGFR tyrosine kinase inhibitor (TKI)) probably makes little or no difference in overall survival (hazard ratio (HR) 0.99, 95% confidence interval (CI) 0.81 to 1.20; one study; 835 participants; low‐certainty evidence) and may make little or no difference in progression‐free survival (HR 1.05, 95% CI 0.90 to 1.23; one study; 835 participants; very low‐certainty evidence). Less than 50% of participants provided quality of life data, and study authors reported these results incompletely. The certainty of evidence is very low, but treatment may reduce quality of life compared to observation. Treatment with an EGFR TKI (vandetanib) for women with relapsed EOC may make little or no difference in overall survival (HR 1.25, 95% CI 0.80 to 1.95; one study; 129 participants; low‐certainty evidence) and may make little or no difference in progression‐free survival (HR 0.99, 95% CI 0.69 to 1.42; one study; 129 participants; very low‐certainty evidence). In treating patients with relapse, giving EGFR TKI may slightly increase some toxicities, such as severe rash (risk ratio (RR) 13.63, 95% CI 0.78 to 236.87; one study; 125 participants; very low‐certainty evidence). Quality of life data were not available for meta‐analysis. Anti‐EGFR antibody treatment in relapsed EOC may or may not make a difference to overall survival (HR 0.93, 95% CI 0.74 to 1.18; four studies; 658 participants; moderate‐certainty evidence) and may or may not have any effect on progression‐free survival (HR 0.90, 95% CI 0.70 to 1.16; four studies; 658 participants; low‐certainty evidence). Anti‐EGFR antibody treatment may or may not increase side effects, including severe nausea and/or vomiting (RR 1.27, 95% CI 0.56 to 2.89; three studies; 503 participants; low‐certainty evidence), severe fatigue (RR 1.06, 95% CI 0.66 to 1.73; I² = 0%; four studies; 652 participants; low‐certainty evidence), and hypokalaemia (RR 2.01, 95% CI 0.80 to 5.06; I² = 0%; three studies; 522 participants; low‐certainty evidence). Severe diarrhoea rates were heterogeneous across studies (RR 2.87, 95% CI 0.59 to 13.89; four studies; 652 participants; low‐certainty evidence), and subgroup analysis revealed that severe diarrhoea was more likely with pertuzumab (RR 6.37, 95% CI 1.89 to 21.45; I² = 0%; three studies; 432 participants; low‐certainty evidence) than with seribantumab treatment (RR 0.38, 95% CI 0.07 to 2.23; I² = 0%; one study; 220 participants; very low‐certainty evidence). Quality of life data were incompletely reported, and we were unable to combine them in a meta‐analysis. Authors' conclusions: Current evidence suggests that an anti‐EGFR single‐agent biological treatment (EGFR TKI or anti‐EGFR antibody) makes little or no difference to survival, either as maintenance treatment after first‐line chemotherapy or in association with chemotherapy in recurrent cancer. Anti‐EGFR therapy may increase some side effects and may or may not reduce quality of life.